2004
DOI: 10.1111/j.1365-2443.2004.00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Harp (harmonin‐interacting, ankyrin repeat‐containing protein), a novel protein that interacts with harmonin in epithelial tissues

Abstract: Mutations in the triple PDZ domain-containing protein harmonin have been identified as the cause of Usher deafness syndrome type 1C. Independently, we identified harmonin in a screen for genes expressed in pancreatic β β β β cells. Using a yeast two-hybrid assay, we show that the first PDZ domain of harmonin interacts with a novel protein, designated harp for h armonin-interacting, a nkyrin r epeat-containing p rotein. This interaction was confirmed in an over-expression system and in mammalian cells, and show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…As shown in Fig. 4E, FLAG-Anks4b was able to coimmunoprecipitate GRP78 as well as harmonin, a protein that was previously found to interact with Anks4b (25). These results indicated that Anks4b binds to GRP78 in cells.…”
Section: Hnf4␣ and Hnf1␣ Synergistically Activate Transcription Ofsupporting
confidence: 56%
See 2 more Smart Citations
“…As shown in Fig. 4E, FLAG-Anks4b was able to coimmunoprecipitate GRP78 as well as harmonin, a protein that was previously found to interact with Anks4b (25). These results indicated that Anks4b binds to GRP78 in cells.…”
Section: Hnf4␣ and Hnf1␣ Synergistically Activate Transcription Ofsupporting
confidence: 56%
“…Reporter gene assays and ChIP analysis demonstrated that HNF4␣ bound to a conserved HNF4 binding motif and activated transcription, thus indicating that Anks4b is a direct target of HNF4␣ in ␤-cells. In addition to the pancreatic islets, Anks4b is also expressed in the liver, kidney, small intestine, and colon (25). This distribution of expression is very similar to that of HNF4␣, suggesting that HNF4␣ plays a role in Anks4b gene transcription in these tissues.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…11,88,109,114116 In addition, we and others have shown that the association of other proteins with the USH complex through harmonin indicates that the complex may be functionally linked to a number of basic cell-biological processes, including cell polarity and cell–cell interactions. 117,118 On the basis of the analysis of the whirler mutant and the expression pattern of whirlin in the inner ear, it was hypothesized that whirlin may coordinate F-actin growth. 72 Both CDH23 and PCDH15 are components of transient lateral links, kinociliary links and tip links in the inner ear sensory cells, 89,91,92,119,120 are therefore thought to be crucial for morphogenesis and mechanotransduction.…”
Section: The Ush Proteins Interact To Control the Morphogenesis Of Hamentioning
confidence: 99%
“…15,22 ANKS4B was originally identified as a USH1C binding protein that is highly expressed in epithelial tissues. 23 Cell biological studies and biochemical characterization of ANKS4B binding to other IMAC components revealed new insights on the multivalent interactions that drive IMAC assembly, distal tip targeting, and intermicrovillar adhesion. 15 Knockdown of ANKS4B in epithelial cells led to a striking loss of all other IMAC components from microvillar tips; ANKS4B knockdown cells were essentially null for the entire IMAC.…”
Section: The Imac Gets a New Membermentioning
confidence: 99%